Research on the Impact of Technology on Policing Strategy, 2012-2014 (United States) - Strom, Kevin ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The purpose of this study was to develop a research-based framework to guide police agencies in future selection, implementation, and use of technology. This project was conducted in three phases. First, an expert panel was convened to identify key policing technology and to ensure that the survey captured critical indicators of technology performance. Second, a nationally representative survey was administered to over 1,200 state and local law enforcement agencies. The survey explored policing strategies and activities as well as technology acquisition, use, and challenges.